A hypoxic ticket to the bone metastatic niche. Issue 1 (December 2015) - Vanharanta, Sakari
Abstract Hypoxia is a well-characterized driver of aggressive cancer phenotypes, including metastasis. Accumulating evidence suggests that, in addition to having local effects, the consequences of tumour hypoxia can be systemic, leading to the formation of pre-metastatic niches that can later foster metastatic colonization in distant organs. Recent findings have demonstrated that such niches can also form in the bone, possibly revealing new avenues for therapeutic intervention.